Preliminary Cross-Sectional Screening for the Assessment of Macronutrient Consumption and Body Mass Index in Orphans Aged 7 to 15 Years in Amman, Jordan - Hadeel Ghazzawi (مجلة جامعة النجاح للأبحاث العلوم الطبيعية)
The aim of this study was to screen for malnutrition by evaluating macronutrient intake and calculating the ratio of body mass index (BMI) to age of orphans in 7 selected governmental orphanages in Amman, Jordan. The study recruited 277 orphans, including 156 girls and 121 boys aged 7 to 15 years. Nutritional assessments (BMI and 3 days food recall) were recorded by trained nutritionists. Macronutrient content was analyzed by EISHA software. The ratio of BMI to age among orphans was at the lower end of the normal range for boys and girls, at 18.8 and 20.73, respectively. The macronutrient daily intake of orphans met the requirements for their age groups. The majority of assessed orphans from orphanages in Amman had proper body weights and met the recommendations for macronutrient and energy intake. However, eating habits should be improved. Changes should be applied to improve the provision of nutrient-dense foods to orphanages. In summary, our study shows that orphans in Amman do not suffer from malnutrition, but their dietary quality should be adjusted.